2013
DOI: 10.1021/ac402624a
|View full text |Cite
|
Sign up to set email alerts
|

Peak Distortion Effects in Analytical Ion Chromatography

Abstract: The elution profile of chromatographic peaks provides fundamental understanding of the processes that occur in the mobile phase and the stationary phase. Major advances have been made in the column chemistry and suppressor technology in ion chromatography (IC) to handle a variety of sample matrices and ions. However, if the samples contain high concentrations of matrix ions, the overloaded peak elution profile is distorted. Consequently, the trace peaks shift their positions in the chromatogram in a manner tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Similarly competitive isotherms may also lead to fronting and unique peak shapes. Such peak shapes were reported for ion chromatography . Injecting large enough mass of solute on the column may cause a part of the solute to travel ahead of the main band and emerge as a breakthrough, giving rise to a fronting peak profile.…”
Section: Resultssupporting
confidence: 52%
“…Similarly competitive isotherms may also lead to fronting and unique peak shapes. Such peak shapes were reported for ion chromatography . Injecting large enough mass of solute on the column may cause a part of the solute to travel ahead of the main band and emerge as a breakthrough, giving rise to a fronting peak profile.…”
Section: Resultssupporting
confidence: 52%
“…High concentrations of chloride ions are known to interfere with ion chromatographic systems, overloading the detectors. This overload causes peak distortions and poor component separation (Wahab et al, 2014). One solution to this problem is to dilute samples to mitigate concentration overload.…”
Section: Ion Chromatographymentioning
confidence: 99%
“…Recent studies [41] have shown that mass overload of analyte on modern ion chromatography columns obeys a competitive Langmiur isotherm behavior, in which both analytes and strongly adsorbed mobile phase components compete for sorption sites [38,42]. For Langmuir isotherms, the competitive situation is described by:…”
Section: Discussionmentioning
confidence: 99%